APOE DNA methylation is altered in Lewy body dementia. Issue 7 (12th March 2018) - Tulloch, Jessica; Leong, Lesley; Chen, Sunny; Keene, C. Dirk; Millard, Steven P.; Shutes‐David, Andrew; Lopez, Oscar L.; Kofler, Julia; Kaye, Jeffrey A.; Woltjer, Randy; Nelson, Peter T.; Neltner, Janna H.; et al.
Abstract: Introduction: Inheritance of the ε4 allele of apolipoprotein E ( APOE ) increases a person's risk of developing both Alzheimer's disease (AD) and Lewy body dementia (LBD), yet the underlying mechanisms behind this risk are incompletely understood. The recent identification of reduced APOE DNA methylation in AD postmortem brains prompted this study to investigate APOE methylation in LBD. Methods: Genomic DNA from postmortem brain tissues (frontal lobe and cerebellum) of neuropathological pure (np) controls and npAD, LBD + AD, and npLBD subjects were bisulfite pyrosequenced. DNA methylation levels of two APOE subregions were then compared for these groups. Results: APOE DNA methylation was significantly reduced in npLBD compared with np controls, and methylation levels were lowest in the LBD + AD group. Discussion: Given that npLBD and npAD postmortem brains shared a similar reduction in APOE methylation, it is possible that an aberrant epigenetic change in APOE is linked to risk for both diseases.